1981
DOI: 10.1073/pnas.78.10.5983
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of the genome of poliovirus type 1.

Abstract: Poliovirus cDNA RNA hybrids were prepared from the Mahoney strain ofpoliovirus type 1 by using reverse transcriptase (RNA-dependent DNA nucleotidyltransferase) and cloned in the Escherichia coliplasmidpBR322. Bacteria colonies carrying recombinant plasmids were selected by in situ hybridization with virus-specific RNase Ti-resistant oligonucleotides. Analysis of the cDNA inserts by restriction mapping and electron microscopy showed that the cloned cDNAs, the longest of which was 3.2 kIlobase pairs, originated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…The nucleotide sequence of this extended material was determined chemically (14). Comparison of the sequence with that of the previously established 5'-terminal sequences (15)(16)(17) indicated that the extension proceeded to the very 5' end of the viral genome. Sequence analysis of the EB1 fragment in a plasmid pVS(1)EB1 revealed that this insert contained the sequence corresponding to that ofthe first 220 bases of the viral genome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nucleotide sequence of this extended material was determined chemically (14). Comparison of the sequence with that of the previously established 5'-terminal sequences (15)(16)(17) indicated that the extension proceeded to the very 5' end of the viral genome. Sequence analysis of the EB1 fragment in a plasmid pVS(1)EB1 revealed that this insert contained the sequence corresponding to that ofthe first 220 bases of the viral genome.…”
Section: Resultsmentioning
confidence: 99%
“…1). van der Werf et al (15) have succeeded in the direct cloning of the 5' end ofpoliovirus RNA using RNADNA hybrids. Because we were unable to obtain directly 5'-terminal clones, we used a restriction fragment (positions 221-267) from clone pVS(1)BB3 that was 5'-end-labeled and employed as a primer to synthesize a primer extension fragment.…”
Section: Resultsmentioning
confidence: 99%
“…In one instance it was possible to obtain a complete set of subgenomic clones of polio cDNA from a single cycle of cloning (van der Werf et al, 1981). Similarly, reverse transcriptions of in vitro polyadenylated Rift Valley virus RNA with oligo dT as primer yielded cDNA transcripts internal to the viral genome (J. Dalrymple and C. Schmaljohn, personal communication).…”
Section: B Research Personnel Comprising the Project Teammentioning
confidence: 99%
“…To (17) and subeloned within the P-lactamase gene of pBR322. As the VP1 sequence contains no initiator AUG triplet, being located internally in the poliovirus genome (22)(23)(24), it was necessary to fuse it in phase behind the AUG of the f3-lactamase gene.…”
mentioning
confidence: 99%
“…The minicell-producing strain GC26 (Bl-thrleu-) was kindly provided by G. Cesareni. Plasmids pPV1-366 and pSW1l9 have been described (15,17).Construction of Plasmids. Plasmid DNA was cleaved by restriction endonucleases following manuicturers' conditions.…”
mentioning
confidence: 99%